2017
DOI: 10.3892/or.2017.5928
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein inhibits choriocarcinoma proliferation by arresting cell cycle at G1 phase through suppressing ERK pathway in vitro and in vivo

Abstract: Choriocarcinoma is a highly malignant tumor arising from abnormal gestational trophoblast proliferation. Although chemotherapy has dramatically improved the prognosis, there are still some patients who become drug-resistant or relapse. Daidzein has garnered interest in its antitumor activity especially in proliferation inhibition. However, few reports exist on daidzein effect in growth of choriocarcinoma. Therefore, in this study, we performed in vitro and in vivo experiment in JAR and JEG‑3 to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…In choriocarcinoma, daidzein regulates production of human chorionic gonadotropin (27) and, as demonstrated in the authors' previous study, also inhibits cell proliferation (28). In the present study, in vitro experiments were performed to determine whether daidzein exhibits a pro-apoptotic effect on choriocarcinoma cells.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In choriocarcinoma, daidzein regulates production of human chorionic gonadotropin (27) and, as demonstrated in the authors' previous study, also inhibits cell proliferation (28). In the present study, in vitro experiments were performed to determine whether daidzein exhibits a pro-apoptotic effect on choriocarcinoma cells.…”
Section: Discussionmentioning
confidence: 66%
“…Jeschke et al (27) observed a significant concentration-dependent decrease in production of human chorionic gonadotropin in trophoblast cells treated with daidzein. Furthermore, the authors previously demonstrated the anti-proliferation activity of daidzein in choriocarcinoma (28). However, few studies regarding the effect of daidzein on apoptosis have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Following another 48 h of culture, the transfected cells were harvested and the ANGPTL4 expression was quantified using RT-qPCR. Activation of the ERK pathway was performed by treatment with 10 µM of Ceramide C6 (Santa Cruz Biotechnology, Santa Cruz, CA, USA) 13 . The cells were divided into shCtr group (transfected with silencing negative control plasmid), shANGPTL4 group (transfected with shANGPTL4 plasmid), control group (transfected with negative control overexpression plasmid), ANGPTL4 group (transfected with oe-ANGPTL4 plasmid), and ANGPTL4 + Ceramide C6 group (transfected with oe-ANGPTL4 plasmid + Ceramide C6).…”
Section: Methodsmentioning
confidence: 99%
“…The literature review revealed that flavonoids target and positively affect three pathways in GI cancer. Diazedine could inhibit choriocarcinoma cellular proliferation through the suppression of the extracellular-signal-regulated kinase (ERK) pathway by inhibiting p-ERK expression and translocation, as illustrated in Figure 7 [126]. Additionally, Figure 8 illustrates the mechanisms in which the metastasis of colon cancer was inhibited after the administration of dietary delphinidin.…”
Section: Flavonoids Effects On Impaired Specific Pathwaysmentioning
confidence: 99%